2012
DOI: 10.4028/www.scientific.net/amr.605-607.1356
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Transmissivity of Electromagnetic Wave in Magnetorheological Fluids

Abstract: The internal structure of magnetorheological fluid could change under external magnetic field, as well as its dielectric constant and magnetic conductance. A theoretical model of electromagnetic wave propagation in MRF was established and the basic formula of transmissivity was deduced. Theoretical simulation shows that the electromagnetic wave transmissivity decreases with the increasing of dielectric constant of magnetorheological fluid, and increases with the magnetic permeability. Theoretical analysis indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Based on the formation of clustering structures inside MR fluid clearly had an influence on ultrasonic propagation, Bramantya et al [23,24] proposed a qualitative analysis of these clustering structures by measuring properties of ultrasonic propagation. Wan et al [25] established a theoretical model of electromagnetic wave propagation in MR fluid, the results showed that the electromagnetic wave transmissivity decreased with the increase of dielectric constant of MR fluid, and increased with the increase of the magnetic permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the formation of clustering structures inside MR fluid clearly had an influence on ultrasonic propagation, Bramantya et al [23,24] proposed a qualitative analysis of these clustering structures by measuring properties of ultrasonic propagation. Wan et al [25] established a theoretical model of electromagnetic wave propagation in MR fluid, the results showed that the electromagnetic wave transmissivity decreased with the increase of dielectric constant of MR fluid, and increased with the increase of the magnetic permeability.…”
Section: Introductionmentioning
confidence: 99%